Islamic Digital Banking Based on Maqasid Al-Shariah for Financial Inclusion: A Proposed Framework - Muhammad Ridhwan Ab. Aziz; Mohd Zalisham Jali; Mohd Nazri Mohd Noor; Syahnaz Sulaiman; Mohd Shukor Harun; Muhammad Zakirol Izat Mustafar (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM), 2024)
10th INTERNATIONAL ISLAMIC ECONOMIC SYSTEM CONFERENCE 2023 (I-iECONS 2023) “Sustainable Development through Innovative Economic Transformation”/ Editors : Amalina Mursidi, Agoos Munalis Tahir, Suhaida Herni Suffarruddin, Norfhadzilawati Rahim, Murad Ali Ahmad Al-Zaqeba, Muhammad Iqmal Hisham Kamaruddin Conference Dates: August 14 2023 I Conference Location: Millennium Makkah Al Naseem Hotel Mecca Saudi Arabia Organized by Faculty of Economics and Muamalat